Pengaruh Intensitas Pencahayaan Terhadap Kelelahan Mata Dan Produktivitas Kerja Pada Tenaga Kerja Di Bagian Sigaret Kretek Tangan (Skt) Pt. Djitoe Indonesia Tobako Surakarta - Sunaryati, Etik; , dr. Hardjanto, M.S., Sp.OK; , Tarwaka, PGDip Sc, M.Erg (2015)
PT. Djitoe Indonesia Tobako is a Company in Surakarta focusing on tobacco products. The quality and time to fullfillment the productions require a preciseness. The purpose of this research is to find the influence of intensity lighting to fatigue eyes and labor productivity at the skt PT.Djitoe Indonesia Tobacco. The kind of research used in this research was Quasi experimental to a draft the research uses one group pretest postest The population of this study was all workers as part SKT 118 respondents. the selection of sample uses purposive sampling of 40 respondents. The results of statistical tests showed there is a difference in intensity lighting to fatigue eyes workers part skt before and after treatment the addition of intensity lighting obtained value p-value (0,000<0.05 ). And from the statistics on productivity show any impact on the intensity of productivity on workers at skt before and after treatment additional intensity lighting obtained value p-value ( 0,000>0.05 ). Thus can be concluded that there are significant influence between the intensity of lighting to fatigue eyes and productivity work in labor part SKT PT. Djitoe Indonesia Tobako